Pengaruh Psikoedukasi Terhadap Masalah Psikososial pada Penderita Kusta dengan Kecacatan di Wilayah Kerja Puskesmas Karang Penang dan Puskesmas Omben - Sholiha, Hilyatus; Jatimi, Atika (Indonesian Health Science Journal, 2024)
Intoduction : Leprosy is a disease that attacks the skin and causes wounds to the skin, peripheral nervous system that will cause nerve damage, muscle weakness and numbness, mucous membranes in the upper respiratory tract and eyes. Objectives : The purpose of this study is to find out the Influence of Psychoeducation on Psychosocial Problems in Leprosy Patients with Disabilities in the Working Area of the Karang Penang Health Center and the Omben Health Center. Method : The research design used is using One Gruops Pretest-Posttest Design with pra experiment. The population of this study is all leprosy patients in the Working Area of the Karang Penang Health Center and Omben Health Center totaling 37 people. The sampling technique in the study uses the probability sampling technique method, simple random sampling where each member of the population has the same probability or chance to be sampled and then measured with a psychosocial problem questionnaire, the data obtained is then analyzed using the Wilcoxson test. Results : The results of the study were obtained that the influence of psychoeducation on psychosocial problems to leprosy patients had results (p=0.03) which means that the p value was less than alpha (a=0.05). Conclution : The conclusion of this study is that psychoeducation can reduce psychosocial problems experienced by leprosy patients.